2009
DOI: 10.1111/j.1600-0404.1990.tb01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of antibiotically treated and untreated neuroborreliosis

Abstract: Follow‐up of 57 patients who suffered from antibiotically untreated acute, monophasic neuroborreliosis 5 to 27 years ago shows no significant difference in comparison with the follow‐up of 66 patients who suffered from antibiotically treated acute, monophasic neuroborreliosis during the last 5 years. In both groups, the involution of clinical symptoms and the normalization of pathological CSF findings were nearly identical. We found no significant difference of sequelae between the groups. Following acute neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…Sixteen publications met our inclusion criteria ( Fig. 1) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]; 17 single-arm studies were considered for descriptive analysis (Appendix S2 and Table S1). Eighty-six articles were excluded (reasons are listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen publications met our inclusion criteria ( Fig. 1) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]; 17 single-arm studies were considered for descriptive analysis (Appendix S2 and Table S1). Eighty-six articles were excluded (reasons are listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most common neurological manifestations of LNB in European children are acute facial nerve palsy (55–61%), other cranial nerve palsies, and lymphocytic meningitis (27%) [ 4 8 ]. Signs and symptoms of early LNB typically last for less than 6 months, and the natural course of the disease is often self-limiting [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequately treated neuroborreliosis in children seems to have an excellent prognosis (Christen et al, 1993;Thorstrand et al, 2002). The duration of persistent symptoms in patients with neuroborreliosis if antibiotic treatment is not given has been estimated to be three to six months in most cases (Kr€ uger et al, 1990), although in some patients continuing and progressive infection may occur (Bensch et al, 1987). In a long-term follow-up study of adult patients many years after untreated neuroborreliosis, Kr€ uger et al observed that 18% of the patients exhibited "mild to medium sequelae" up to 21 years after acute illness, while 32% had mild clinical sequelae (Kr€ uger et al, 1989).…”
Section: Prognosis and Outcomementioning
confidence: 99%